Quality of life, exercise capacity, cognition, and mental health of Chilean patients after COVID-19: an experience of a multidisciplinary rehabilitation program at a physical and rehabilitation medicine unit - Paéz, Valeria; Rodriguez-Fernandez, Maria; Morales, Diego; Torres, Camillo; Ardiles, Andrés; Soza, Sergio; Bustos, Cynthia; Manríquez, Fernanda; García, Cesar; Rocco, Rossana; Lang, Morin (Frontiers in Rehabilitation Sciences, 2023)
Background Post-COVID disabilities, encompassing physical, cognitive, and psychological aspects, constitute the primary health sequelae for survivors. While the rehabilitation needs post COVID-19 are now well understood, each country possesses unique characteristics in terms of populations, healthcare systems, social dynamics, and economic profiles, necessitating context-specific recommendations. This study aims to address two main objectives: (1) analyze the impact of an 8-week multidisciplinary rehabilitation program on the quality of life, functional capacity, cognition, and mental health adaptations in adults recovering from COVID-19 in northern Chile, and (2) propose a personalized model for predicting program dropouts and responses. Methods A total of 44 subjects were enrolled, forming two groups during the study: a treatment group (n = 32) and a dropout group (n = 12). The treatment group participated in the 8-week multidisciplinary rehabilitation program. Results The results indicate that (1) After 8 weeks, the quality of life of the patients in the treatment group exhibited significant improvements reflected in all aspects of the Short Form-36 Health Survey (SF36, p < 0.005) and the total score (p < 0.001), with a concurrent decrease in dysfunctionality (p < 0.001). (2) Significant improvements were also observed in various physical performance tests, including the: 6-minute walk test, 1-min sit-to-stand, dynamometry, Tinetti balance, and Berg score (p < 0.001). Moreover, physical therapy led to a reduction in neuropathic symptoms and pain, psychological therapy reduced anxiety and depression, and language therapy enhanced memory and speech (all p < 0.05). (3) Demographic and clinical history characteristics did not predict responses to rehabilitation. (4) A regression model for predicting changes in SF-36 total score, based on physical function, physical role, general health, and mental health, was established based on the data from study (p < 0.01, adjusted R2 = 0.893). (5) Classification models for predicting dropouts achieved 68% accuracy, with key predictors of treatment adherence including diabetes, hypertension, and dyslipidemia, Tinetti balance, physical role, and vitality of SF36, and performance on the 6-minute walk test and 1-minute sit-to-stand. Conclusions This study demonstrates significant enhancements in quality of life, improved functional performance, and reductions in mental and cognitive burdens within an 8-week rehabilitation program. Additionally, it is possible to identify patients at risk of dropping out using cost-effective, outpatient, and clinically applicable tests.